Análisis crítico del procedimiento coactivo y juicio de excepciones dentro de la legislación ecuatoriana - Hurtado Troya, Guillermo Andrés (2013)
The Titration present work, have the purpose of analysis of Coactive process of Judge of Exceptions, with they are own legal consequences either for the tax Administration as for the tax payer as well. The particular analysis was made for the reasons that have the Administration for the Title of Credit and the initiation of the coactive actions against of the tax payers that did not pay the liabilities that they owe. In reference at the coactive procedure, it was exposed the respective measures to collect the taxes, like the seizure, auction of the goods of the tax tributary debtor. The third-party help and exclusives that can ask for interpose for the third damaged. Respect to the competition of the tax, we were materialized in the analysis of the exceptions, like an issue of the knowledge from the Tax Court, the proceed of the same until reach the sentences. Finally, it was realized the analysis of the Law of Promotion Environmental Optimization of the income of the State, in particular of the tenth transitional disposition whose application inflicted legal drawbacks.